Adolescents in Humanitarian Crisis Displacement, Gender and Social Inequalities - Jones, Nicola; Pincock, Kate; Hamad, Bassam Abu (Routledge Humanitarian Studies, 2021)
Adolescents in Humanitarian Crisis investigates the experiences of adolescents displaced by humanitarian crisis. The world is currently seeing unprecedented levels of mass displacement, and almost half of the world's 70 million displaced people are children and adolescents under the age of 18. Displacement for adolescents comes with huge disruption to their education and employment prospects, as well as increased risks of poor psychosocial outcomes and sexual and gender-based violence for girls. Considering these intersectional vulnerabilities throughout, this book explores the experiences of adolescents from refugee, internally displaced persons and stateless communities in Bangladesh, Ethiopia, Jordan, Lebanon, Palestine and Rwanda. Drawing on innovative mixed-methods research, the book investigates adolescent capabilities, including education, health and nutrition, freedom from violence and bodily integrity, psychosocial wellbeing, voice and agency, and economic empowerment. Centring the diverse voices and experiences of young people and focusing on how policy and programming can be meaningfully improved, this book will be a vital guide for humanitarian students and researchers, and for practitioners seeking to build effective, evidence-based policy.